Descriptivism and Its Discontents. Issue 2 (April 2017) - DAVIES, DAVID
Abstract: Is ontologizing about art rightly held accountable to artistic practice, and, if so, how? Julian Dodd argues against such accountability. His target is "local descriptivism, " a meta‐ontological principle that he contrasts with meta‐ontological realism. The local descriptivist thinks that folk‐theoretic beliefs implicit in our practices somehow determine the ontological characters of artworks. I argue, however, that according a grounding role to artistic practice in the ontology of art does not conflict with meta‐ontological realism. Practice must ground our ontological inquiries because our task is to make sense of the practices into which artworks enter. Terms like 'musical work, ' as employed by the ontologist, play an essentially explanatory role in this endeavor, and it is only in terms of this role that we can specify the object of our ontological inquiries. But neither our practices nor our folk beliefs are sacrosanct. In taking ontology of art to be reflectively accountable to artistic practice, I also reject Amie Thomasson's claim that it involves conceptual analysis and therefore cannot rightly claim to be directly revisionary of folk understandings. Ontology of art involves not conceptual analysis but the codification of a practice in a way that clarifies that practice.